The mechanical behavior of two warm-mix asphalts (2016)
This paper presents results stemming from a comparative experimental analysis of two warm-mix asphalts (WMA) and a dense-graded hot-mix asphalt (HMA). In order to evaluate asphalt mixture behavior, physical and rheological tests were conducted, including tests on resilient modulus, resistance to moisture-induced damage, resistance to fatigue and resistance to permanent deformation. Samples studied were subjected to short (STOA) and long-term (LTOA) aging. As far as asphalt mixture composition is concerned, the same particle size distribution and coarse aggregate were employed for both mixture types. The control HMA mixture was produced with AC 60-70, and the WMAs used the same asphalt cement modified with two chemical additives (Rediset WMX® and Cecabase RT®). The modified mixtures exhibited better resistance to permanent deformation, aging and moisture-induced damage (versus the control mixture). Likewise, WMAs generally saw increased fatigue resistance under controlled-stress loading, which rheological characterization showed is mainly attributable to binder additives and their concomitant modifications.